End-user procedure for the calibration of an X-Rays fluorescence spectrometer - Roveratti, Gabrielle; Bonotto, Daniel Marcos [UNESP] (My University, 2017)
UNESPetro (Geosciences Center Applied to Petroleum), IGCE (Geosciences and Exacts Sciences Institute), UNESP (São Paulo State University), Rio Claro, São Paulo State, Brazil, acquired S8 Tiger X-Ray Fluorescence (XRF) Spectrometer from Bruker Co. for performing chemical analysis of rocks, minerals, ores, soils and sediments. Two analytical softwares came with the equipment: one aimed to pressed (powdered) samples, QuantExpress, and another to fused samples, GeoMaj. Other calibration steps are required if the user requests additional analysis not included in such packages, according to the specific needs. This chapter reports the results obtained for the implementation of a new procedure to enlarge the analytical capacity of such instrument beyond of that foreseen by both softwares, thus, allowing the specific elements analyses in additional concentration intervals. Tests employed fused beads, under the same experimental conditions of voltage and current, i.e., 30 kV and 5 mA, respectively. The selection of the interest elements happened by the Application Wizard software available in the equipment. Then, it was inserted the oxides concentration of the standards and defined the selected variables (adopted parameters, standards units, size, possible contamination, etc.). Parameters such as correlation deviation, overlap adjust, concentration unit, interval selection, results presentation, among others allowed to build the calibration curves. The method implementation used ten standards: cement, clay, feldspar, limestone, dolomite, sylvanite, magnesite, sediments and two different rock types. The acquired results indicated that the adopted procedure for the instrumental calibration starting from the end-user showed up suitable, increasing the analytical potentiality of the XRF spectrometer in order to analyze elements of interest in geochemical studies.